A Study of 3, 5‐Dinitro‐1‐(2, 4, 6‐trinitrophenyl)‐1H‐pyrazol‐4‐amine (PicADNP) as a New High Energy Density Booster Explosive. Issue 13 (25th March 2021) - Bauer, Daniel; Dosch, Dominik E.; Fuchs, Veronika; Karaghiosoff, Konstantin; Klapötke, Thomas M.
Abstract: Two improved, fast, feasible, scalable, and economic synthetic protocols for the laboratory scale manufacturing of 3, 5‐dinitro‐1‐(2, 4, 6‐trinitrophenyl)‐1H‐pyrazol‐4‐amine (PicADNP) are described. The previous set of analytical data from an earlier publication could be verified and complemented by additional measurements. The material was fully characterized by multinuclear NMR, spectroscopic methods, elemental analysis, DSC and DTA, as well as X‐ray diffraction. The crystal structure was elucidated and Hirshfeld surface analysis, as well as 2D fingerprint plot analysis for the assessment of sensitivities towards external stimuli was applied. The sensitivity towards shock, friction and electrostatic discharge was also determined experimentally. The performance of the title compound was calculated by applying the EXPLO5 computer code and the theoretical results were compared with the results of SSRT and booster testing experiments. The title compound combines good energetic properties with improved safety characteristics and could find its way into application as a new booster explosive to replace the state‐of‐the‐art material PETN. The optimizations of the synthetic protocol comprise a greener solvent system, shorter reaction times, higher yields for the pure material and a nontoxic byproduct to make the manufacturing process more attractive and better suitable for a subsequent scale up to the technical and industrial scale. Abstract : Two optimized synthetic pathways for the manufacturing of 3, 5‐dinitro‐1‐(2, 4, 6‐trinitrophenyl)‐1H‐pyrazol‐4‐amine (PicADNP) are described. The material was fully characterized, and its crystal structure could be elucidated. Hirshfeld surface and 2D fingerprint plot analysis were performed to assess the sensitivity towards external stimuli. Various energetic properties were calculated and compared to the results of sensitivity measurements, SSRT testing and booster testing.